Elizabeth Gunner, Radio Soundings: South Africa and the Black Modern - Kobokana, Siyanda (Kronos: Southern African Histories, 2024)
In the face of the Zondo Commission’s horrific and horrifying news about the capture of state-owned enterprises such as Eskom, Prasa, and SABC, commentators claim the capture was the outcome of Jacob Zuma’s ‘nine squandered years’. The same capture similarly happened under apartheid. Furthermore, the apartheid state wielded considerable control and regulation over state firms through its regulatory and control mechanisms. During apartheid South Africa, prior to the years of what we now term state capture, a special capture of the Black people’s voice occurred, as did a special capture of the auditory, a capture of SABC radio sound by apartheid authorities. This was a state capture of a different kind, one meant for control rather than corruption. As a state-owned corporation, the SABC, I would argue, was likewise captured by the apartheid regime with this level of control. Radio capture became a significant instrument for the apartheid regime as they sought to dominate the Black community through domination rather than consent.